Esensi Makna Di Sebalik Cawet: Studi Toponimi Penamaan Dusun Di Desa Surengede Wonosobo - Bambang Sugiyanto; Robingun Suyud El Syam; Salis Irvan Fuadi (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This research is to reveal the essence of the meaning behind cawet: a toponymic study of the naming of hamlets in the village of Sungede Wonosobo, by emphasizing the historical aspects of the facts on the ground. This article is a finding from descriptive research using onomastic theory, then analyzed historically to see its essence. The results of the study show that the naming of the cawet hamlet in Sungede village, Wonosobo district, is the name given by a hero who led the local community when expelling the Dutch colonialists named Simbah Cahyuda. The naming was based on the spirit so that future generations would not forget the services of the soldiers who in war some only wore cawet bare-chested. The implication of the research, our narrative experience brings understanding to the essence of a struggle not to see the physical but the essence of the action. The research is expected to contribute to the scientific history of Islamic education.